Liquid smoke to Control Bulkholderia glumae and Growth Promoter of Rice Seeds - Nurfadillah; Giyanto, Giyanto; Mutaqin, Kikin Hamzah; Damayanti, Tri Asmira (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2022)
Liquid smoke to Control Bulkholderia glumae and Growth Promoter of Rice Seeds Bacterial grain rot disease caused by Bulkholderia glumae is an important disease that can be transmitted through rice seeds. Various bacterial grain rot disease control techniques have been developed to prevent crop loss, one of which is liquid smoke. Liquid smoke has been widely studied as an agent for controlling various plant diseases. The aim of the study was to determine the potential of liquid smoke to control bacterial grain rot disease caused by B. glumae and to promote the growth of rice seedlings. Research was conducted in some stages, included: potential test of liquid smoke against B. glumae, phytotoxicity test of liquid smoke and its effect on rice seed growth; and test the effectiveness of liquid smoke in suppressing B. glumae on infected seeds. The results showed that liquid smoke with a concentration of 2% could suppress the development of B. glumae in vitro and did not cause phytotoxicity in rice seeds with a vigor index of 90% and germination of 90% compared to controls with a vigor index value and germination value of 76% and 83%. Liquid smoke with a concentration of 2% can also reduce the severity of disease in the nursery phase with a relative inhibition level of 43.8%. The value of the length of the plumule of rice seedlings in the 2% liquid smoke treatment was 5.87 cm. The plumule value was greater than the control which was only 5.22 cm. In contrast to the plumula, the value of radicular length did not increase significantly compared to the control.